Transient Pneumonitis as a Possible Adverse Reaction to the BNT162b2 COVID-19 mRNA Vaccine in a Patient with Rheumatoid Arthritis: A Case Report and Review of the Literature - Yusuke Ohkubo; Shin-ichiro Ohmura; Ryuhei Ishihara; Toshiaki Miyamoto (Case Reports in Rheumatology)
The coronavirus disease (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 has led to rapid progress in vaccine development to prevent the spread of the disease. Although COVID-19 vaccines have excellent effectiveness in reducing morbidity and disease severity with minor adverse reactions, some patients develop late hypersensitivity events as autoimmune reactions such as rheumatoid arthritis, lupus nephritis, and vasculitis following COVID-19 vaccination. Herein, we describe a case of pneumonitis following COVID-19 mRNA vaccination in a patient with rheumatoid arthritis, which resolved spontaneously.